Length–weight relationships, condition factor and relative condition factor of blood cockle, Tegillarca granosa (L. 1758) collected from the west coast of Cox’s Bazar, Bangladesh - Tanjuma Tasnim Hira; Fauzia Mashkura Nishat; Mahfuza Anika; Sanjida Afrin Semme; Md. Jasim Uddin (Discover Oceans)
Abstract Blood cockle (Tegillarca granosa) is a commercially important bivalve species harvested from aquaculture and natural stocks. Length–weight relationships, condition factor (K) and relative condition factor (K n ) of T. granosa were investigated collected monthly from the intertidal zone on the west coast of Cox’s Bazar, Bangladesh during July 2018-June 2019. A total of 240 individuals shell length (SL) ranging from 3.6 to 6.9 cm, shell height (SH) varying from 3.5 to 5.8 cm, shell thickness (ST) changing from 3.3 to 5.1 cm and tissue wet weight (TWW) deviating from 5.5 to 20.9 g were analyzed. The regression equation established for SL-TWW, SH-TWW and ST-TWW were SL = 0.16 × SL2.476 (r2 = 0.815), TWW = 0.45 × SH2.262 (r2 = 0.681) and ST = 0.43 × ST2.203 (r2 = 538) respectively. Negative allometric growth pattern was inferred from all three different lengths and TWW relationships (b < 3) established for T. granosa of the habitat. SL-TWW exhibited the strongest correlation over SH-TWW and ST-TWW, hence the K and K n values were established applying SL-TWW relationships. The K values varied from 6.05 to 7.57 and the K n values ranged between 0.90 and 1.18. The highest K n value reported in June (1.18) could be the most suitable time for harvesting healthier animals from the habitat. The negative allometric growth patterns observed for different lengths and TWW relationships indicate that T. granosa on the west coast of Cox’s Bazar does not exhibit uniform growth in all dimensions, and shell lengths increase faster than soft tissue growth. The information could be useful by the managers for conservation and sustainable management of the species.